2015
DOI: 10.1111/his.12526
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence in‐situ hybridization identifies Mastermind‐like 2 (MAML2) rearrangement in odontogenic cysts with mucous prosoplasia: a pilot study

Abstract: We identified MAML2 rearrangements in five of nine ODCs lined by mucus-secreting cells. This suggests that at least a subset of ODCs with mucous prosoplasia are characterized by molecular events considered diagnostic for intraosseous and extraosseous MEC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 31 publications
(74 reference statements)
0
22
1
1
Order By: Relevance
“…To our knowledge, such salivary gland tumors have not been studied for MAML2 gene rearrangements. Furthermore, it should be noted that MAML2 rearrangements have been identified in other odontogenic cysts besides GOC, including dentigerous and radicular cysts . These findings demonstrate the limitations of molecular analysis for MAML2 rearrangements in such cystic lesions, despite its potential diagnostic value.…”
Section: Discussionmentioning
confidence: 83%
“…To our knowledge, such salivary gland tumors have not been studied for MAML2 gene rearrangements. Furthermore, it should be noted that MAML2 rearrangements have been identified in other odontogenic cysts besides GOC, including dentigerous and radicular cysts . These findings demonstrate the limitations of molecular analysis for MAML2 rearrangements in such cystic lesions, despite its potential diagnostic value.…”
Section: Discussionmentioning
confidence: 83%
“…In their opinion, this finding lends credence to discredit the putative nature of a glandular odontogenic cyst as a precursor to central mucoepidermoid carcinoma . A very recent study from Mayo demonstrated the presence of MAML2 rearrangements in a small subset of odontogenic cysts with mucous prosoplasia . The fusion transcript has been reported to be present in a limited group of tumors, including mucoepidermoid carcinomas at various sites (bronchiole, cervix, and breast), some Warthin tumors, and clear cell hidradenoma of the skin, but not in other types of malignancies .…”
Section: Discussionmentioning
confidence: 91%
“…However, it must be remembered that absence of this mutation does not exclude a diagnosis of MC; although it is detectable in 80% of low‐grade MC, it is only present in 46% of high‐grade MC. The results of a pilot study of MAML2 rearrangements in odontogenic cysts recently published by Argyris et al . also raise the possibility that the mutation is not specific for MC; five cysts (four dentigerous, one radicular) demonstrated the MAML2 rearrangement of the nine in which hybridisation was successful; it failed in the one GOC included in the study.…”
Section: Discussionmentioning
confidence: 99%